Multiple sclerosis lesion formation and early evolution revisited: A weekly high-resolution magnetic resonance imaging study. (May 2016) - Guttmann, Charles RG; Rousset, Matthieu; Roch, Jean A; Hannoun, Salem; Durand-Dubief, Françoise; Belaroussi, Boubakeur; Cavallari, Michele; Rabilloud, Muriel; Sappey-Marinier, Dominique; Vukusic, Sandra; Cotton, François
Background: Several magnetic resonance imaging (MRI) studies investigated the evolution of multiple sclerosis (MS) lesions to understand the pathophysiological mechanisms leading to blood-brain barrier breakdown and lesion formation. Only a few assessed the early natural history of MS lesions using short-interval longitudinal MRI. Objective: The purpose of this study was to characterize MS lesion occurrence and early evolution on high-resolution MRI acquired at weekly intervals. Methods: Active lesions were characterized on 3D fluid attenuation inversion recovery (FLAIR) and gadolinium-enhanced 3D T1-weighted MRI performed weekly (seven weeks) on five untreated patients with relapsing–remitting MS (RRMS). Results: Active lesions ( n =212) were detected in all patients. All showed contrast-enhancement on at least one time-point. Most new lesions (83.5%) were visible on FLAIR and post-contrast T1-weighted images at first detection; 11.2% showed activity on FLAIR images, one or more weeks before the appearance of contrast-enhancement; 12.5% enhanced before being apparent on FLAIR. Conclusion: Blood brain barrier disruption is a constant step in the natural history of active MS lesions, but does not always constitute the initial event. These findings are consistent with the existence of a subpopulation of lesions with an 'inside-out' genesis, where neurodegenerative processes might precede microglial activation, and a subsequent adaptive immune response.